Changes in the Coverage of Essential Services Along the Rural Provincial Border as a Result of Informal Collaboration - Isti Andini; Achmad Djunaedi; Deva Fosterharoldas Swasto (Geoplanning: Journal of Geomatics and Planning, 2022)
The Sustainable Deveopment Goals prioritize universal essential public services as the second most important development goal after human basic needs in a global perspective. Indonesia implements a public service provision standard with a territorial approach and a set of minimum population requirement that lead to urban bias, resulting in border areas failing to meet the requirements for the provision of public services. Daerah Istimewa Yogyakarta Province is one of Indonesia's provinces with more than 70% of its border areas being rural, and more than 40% of border villages having limited essential public services. Because of the territorial delivery system for essential public services, formal cross-border services require a significant amount of resources. Using quantitative approach by indexing essential public services availability, this paper examines changes of essential public services coverage when cross-border services are provided informally. The case of Pustu Panggang informal crossborder service delivery provides lessons on how informal collaboration works. Although it involves misdeeds and omissions, the application of informal collaboration in cross-border services increases essential public service coverage by 57 percent in Daerah Istimewa Yogyakarta Province's rural border areas. As a result, informal collaboration should be viewed as a low-cost coping strategy in Indonesia's efforts to provide universal public service coverage.